2018
DOI: 10.15671/hjbc.2018.233
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Local Trichoderma spp. as Potential Bio-Control Agents, Screening of in vitro Antagonistic Activities and Fungicide Tolerance

Abstract: T richoderma spp. gibi biyokontrol ajanlarının etkilerini incelemek tarımsal üretimde patojenlerle mücadele yoluyla hastalık kontrolünü sağlamada önemli bir alternatiftir. Bu amaçla, çay bitkilerinin topraklarından izole edilmiş yeşil askosporlara sahip 9 Hypocrea/ Trichoderma türü, ITS sekansları ile tanımlanmış ve türlerin % 77 oranında Trichoderma sect. Pachybasium ile yakın akraba olduğu belirlenmiştir. Fungal izolatların etil asetat ekstraktlarının, Vibrio sp., Serratia marcescens, Mycobacterium smegmatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…It was also found that tolerance activities varied in different plants depending on the types of compounds being used as well as the fungal isolates being employed (Ortiz-Hernández and Sánchez-Salinas, 2010;Chaparro et al, 2011;Singh et al, 2012;Mohiddin and Khan, 2013). An increase in the concentrations of chemical compounds decreased both fungal growth and TI values, which was in accordance with previous findings (Suwannarach et al, 2015;Boat et al, 2018;Karaoglu et al, 2018). In this study, T. phayaoense could tolerate the selected fungicide (metalaxyl) in the field at recommended dosages.…”
Section: Discussionsupporting
confidence: 93%
“…It was also found that tolerance activities varied in different plants depending on the types of compounds being used as well as the fungal isolates being employed (Ortiz-Hernández and Sánchez-Salinas, 2010;Chaparro et al, 2011;Singh et al, 2012;Mohiddin and Khan, 2013). An increase in the concentrations of chemical compounds decreased both fungal growth and TI values, which was in accordance with previous findings (Suwannarach et al, 2015;Boat et al, 2018;Karaoglu et al, 2018). In this study, T. phayaoense could tolerate the selected fungicide (metalaxyl) in the field at recommended dosages.…”
Section: Discussionsupporting
confidence: 93%
“…The agrochemical (herbicides, fungicides, and insecticides) tolerance of fungi varied depending on the type and concentration of agrochemicals, as well as the species and strain of fungi [97,98]. The growth and tolerance capacity of each fungal strain could be decreased by an increase in the agrochemical concentration, which was consistent with previous studies [99][100][101]. In this study, the fungicides (metalaxyl and benomyl) completely inhibited the mycelial growth of all fungi in all concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…The optimum temperature for Trichoderma mycelial growth was observed between 24 and 28 °C, however, in the range of 15 to 24 °C, the temperature was positively correlated with growth rates, followed by a plateau, and the maximum temperature for Trichoderma spp. growth was examined at 32 °C [127]. The results obtained for the DEMTkZ3A0 cultures indicate very high adaptability to temperature conditions of the tested strain, especially in the presence of glucose in the medium.…”
Section: Discussionmentioning
confidence: 99%